2015
DOI: 10.1007/s00167-015-3938-4
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life after open-wedge high tibial osteotomy

Abstract: Prospective case series, II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
1
6

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 43 publications
5
43
1
6
Order By: Relevance
“…Two studies with a low risk of bias reported that patients were unable to work for an average of 19 weeks. This included the study by Saier et al [52], who found that, overall, patients were unable to work for 21 weeks. Separate analysis showed that patients with a concomitant mental disorder could RTW after an average of 36 weeks compared with 16 weeks in the mentally healthy group.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies with a low risk of bias reported that patients were unable to work for an average of 19 weeks. This included the study by Saier et al [52], who found that, overall, patients were unable to work for 21 weeks. Separate analysis showed that patients with a concomitant mental disorder could RTW after an average of 36 weeks compared with 16 weeks in the mentally healthy group.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies described their RTS advice in detail. Three studies [36, 44, 52] advised a return to activities of daily life and low-impact sports after 3 months and a return to more demanding activities and contact sports after 6–12 months. Two studies [38, 49] allowed full RTS, including contact sports, after radiologically confirmed healing of the osteotomy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations